Railways: Gateways Between East and West in Europe - Kuster, Hansjorg (Promet - Traffic&Transportation, 2003)
Railways have connected various far-flung parts of Europefor much of the last two centuries. Recent years, however, haveseen a decline in direct international connections. This is not somuch due to political developments (the Iron Curtain ceased toexist during the period in question), but rather technical advancesthat have resulted in the development of high-speed networksspecific to various countries. Problems associated withthe use of different gauges, and also electrical and sophisticatedelectronic systems in individual European countries have resultedin high-speed trains being confined mainly to individualstates. During the next years, it is highly desirable to re-establishan international European train or Transrapid network to avoidroad and air-traffic chaos as European integration proceedswith the planned eastwards expansion of the European Union.